Modern Information Technologies in Medicine - Sayfullayev Ramziddin Fazliddinovich; Uroqova Ma’mura G‘olibjon qizi; Sanaqulova Marjona Jaxongir qizi; Yuldasheva Zaynab Abdug‘ani qizi; Tilovov Umidjon Bekzod o’g’li (International Journal on Integrated Education, 2023)
The subjects (courses) of "Medical Informatics" are continuous and logical with each other It has been a long time since the idea that it should be connected. But, Unfortunately, up until now, "Informatics" has been studied continuously since school it is a pity that the teaching concept has not been developed.